Amari and the great game - Alston, B. B.; Akpan, Godwin (New York, NY : Balzer + Bray, an imprint of HarperCollins Publishers, 2022)
"After finding her brother and saving the entire supernatural world, Amari Peters is convinced her first full summer as a Junior Agent will be a breeze. But between the fearsome new Head Minister's strict anti-magician agenda, fierce Junior Agent rivalries, and her brother Quinton's curse steadily worsening, Amari's plate is full. So when the secretive League of Magicians offers her a chance to stand up for magiciankind as its new leader, she declines. She's got enough to worry about! But her refusal allows someone else to step forward, a magician with dangerous plans for the League. This challenge sparks the start of the Great Game, a competition to decide who will become the Night Brothers' successor and determine the future of magiciankind. The Great Game is both mysterious and deadly, but among the winner's magical rewards is Quinton's last hope-so how can Amari refuse?"--
Series statement from publisher's webpage.
Ages 8-12.
008-012.
Keywords: Siblings -- Juvenile fiction; Magic -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Magic -- Competitions -- Juvenile fiction; Good and evil -- Juvenile fiction; African Americans -- Juvenile fiction; Siblings -- Fiction; Magic -- Fiction; Blessing and cursing -- Fiction; Magic -- Competitions -- Fiction; Good and evil -- Fiction; African Americans -- Fiction; JUVENILE FICTION / Social Themes / Prejudice & Racism; JUVENILE FICTION / People & Places / United States / African American; JUVENILE FICTION / Fantasy & Magic; African Americans; Good and evil; Magic; Siblings; Paranormal fiction; Siblings -- Juvenile fiction; Occult fiction; Magic -- Juvenile fiction; Good and evil -- Juvenile fiction; African Americans -- Juvenile fiction; Siblings -- Fiction; Magic -- Fiction; Good and evil -- Fiction; African Americans -- Fiction; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works; Paranormal fiction; Fantasy fiction; Paranormal fiction; Fiction